Peripheral Anterior Chamber Depth and Angle Measurements Using Pentacam After Implantation of Toric and Non-toric Implantable Collamer Lenses - Zhao, Jiao; Zhao, Jing; Yang, Wen; Miao, Huamao; Niu, Lingling; Shang, Jianmin; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2021)
Purpose To evaluate the characteristics of peripheral anterior chamber measurements by Pentacam after posterior implantable collamer lenses (ICL) and toric ICL (TICL) with central hole (V4c) implantation. Methods Prospective, non-randomized consecutive case series. Forty-six patients undergoing ICL implantation in one eye (Group A) and identically sized TICL in the contralateral eye (Group B) in the Refractive Surgery Center of Eye and ENT Hospital of Fudan University were prospectively included. According to ICL/TICL size, these eyes were further divided into four subgroups. Peripheral anterior chamber depth (PACD) and angle (ACA) in nasal and temporal sides were measured using Pentacam preoperatively and 12-month postoperatively. Results The safety indices were 1.34±0.32 and 1.25±0.16 and the efficacy indices were 1.20±0.24 and 1.19±0.19 for ICL and TICL groups, respectively. There was no significant difference in preoperative PACD or ACA between the two groups. Postoperative PACD and ACA were significantly lower than preoperative values. Variations of PACD and ACA of TICL group were significantly larger than those of ICL group. The change of ACA for 13.2 mm lenses was significantly larger than that of 12.6 mm lenses. Preoperative CACD and vault were significantly associated with postoperative PACD, while preoperative ACA and vault were significantly associated with postoperative ACA. Conclusions Variations of PACD and ACA were greater in eyes after TICL (V4c) implantation compared with identically sized ICL (V4c) implantation and with larger size than smaller size lens implantation. Preoperative anterior chamber structure and vault affect postoperative PACD and ACA.